2002
DOI: 10.1002/jclp.2006
|View full text |Cite
|
Sign up to set email alerts
|

Personality and deviant sexual fantasies: An examination of the MMPIs of sex offenders

Abstract: A sample of 228 sex offenders and nonsex offender controls were divided into two groups, based on the presence or absence of deviant sexual fantasies, as determined by their replies to the Clarke Sex History Questionnaire Fantasy Scales. The sex offenders were divided into six groups based on sexual preferences and criminal history. There were 14 heterosexual pedophiles, 23 homosexual pedophiles, 51 exhibitionists, 17 incest offenders, 24 sexual aggressives, and 57 multiple/miscellaneous offenders as well as 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 46 publications
1
21
0
9
Order By: Relevance
“…This is also consistent with Chantry and Craig (1994). In our study, sexual offenders were characterized by high lie scale scores and introversion, which is in general accord with Curnoe and Langevin (2002), and Chantry and Craig (1994). The violent offenders displayed more hostile, impulsive, aggressive and psychopathicdeviate characteristics than did sexual offenders and more were considered to pose the greatest risk of reoffending.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is also consistent with Chantry and Craig (1994). In our study, sexual offenders were characterized by high lie scale scores and introversion, which is in general accord with Curnoe and Langevin (2002), and Chantry and Craig (1994). The violent offenders displayed more hostile, impulsive, aggressive and psychopathicdeviate characteristics than did sexual offenders and more were considered to pose the greatest risk of reoffending.…”
Section: Discussionsupporting
confidence: 88%
“…Langevin et al (1988), however, found that, although sex offenders showed more personality pathology compared with other offender groups, there were few differences within sex offender groups. Curnoe and Langevin (2002) divided 228 sex and non-sex offender controls into two groups, based on the presence or absence of deviant sexual fantasies. Using the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) Butcher et al (1989) found deviant fantasizers had more clinically significant scores on the F, Psychopathic Deviate, MasculinityFemininity, Paranoia, and Schizophrenia scales compared with non-deviant fantasizers.…”
Section: Introductionmentioning
confidence: 99%
“…Derivation of pleasure from dominance fantasies may contribute to subsequent use of sexual coercion, at least by sex offenders (Curnoe & Langevin, 2002;Looman, 1995). Although dominance fantasies have also been shown to be associated with coercive sexual behavior among non-criminal men (Gold & Clegg, 1990;Greendlinger & Byrne, 1987), it is unclear whether, for those men, coercive sexual behavior is associated with experiencing cognitions of sexual dominance as positive only, as negative only, or both.…”
Section: Factors Associated With Sexual Dominance Cognitionsmentioning
confidence: 96%
“…Within the few studies that have been conducted, three areas have been of particular focus. These include how certain personality characteristics relate to: (1) the differences between deviant fantasizers and nondeviant fantasizers (Curnoe & Langevin, 2002); (2) the link between deviant fantasies and behavior (Williams et al, 2009); and (3) the adaptive coping strategies used to deal with deviant fantasies (Lussier, Proulx, & McKibben, 2001). …”
Section: Sexual Fantasy and Personalitymentioning
confidence: 99%